2016
DOI: 10.1057/jit.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

Are business users social? A design experiment exploring information sharing in enterprise social systems

Abstract: In recent years, social technology has changed the ways people collaborate and communicate. With the blurring boundaries between work and personal life, business software vendors have begun to deliberate on the possibilities for enhancing the rather rigid and impersonal structures in enterprise systems (ES) by integrating social features. In doing so, they frequently assume that business users share the same interaction patterns as private users. In this paper, we challenge this belief and explore the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 84 publications
0
47
0
Order By: Relevance
“…Another study concerning social features in enterprise systems reveals that business interactions are less social, and highly context specific (Mettler and Winter 2016). Van Osch and Steinfield (2016) showed that the enterprise system user involved in social network posting will show differences in team boundary spanning activities based on their hierarchical position (leadership, team member, etc.).…”
Section: Social Media and Associated Organizational Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study concerning social features in enterprise systems reveals that business interactions are less social, and highly context specific (Mettler and Winter 2016). Van Osch and Steinfield (2016) showed that the enterprise system user involved in social network posting will show differences in team boundary spanning activities based on their hierarchical position (leadership, team member, etc.).…”
Section: Social Media and Associated Organizational Impactmentioning
confidence: 99%
“…In a similar vein, other studies Tow et al 2010) have acknowledged the limitation of restricting their research to a single social media site, and recommend future researchers to adopt a cross-platform perspective for drawing significant inferences. Mettler and Winter (2016) suggest that there is a paucity of studies on Enterprise Social Systems because of its novelty, and urge researchers to fill this void. identify the lack of conceptualization in the notion of technology addiction; they recognize that the process of defining it is still in the early stages, and is being debated across communities.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…A revision or even surveillance strongly influences the privacy of an ESN user. Here recent studies revealed that privacy concerns have a negative impact on the intention to use and sharing behaviors of ESN users [10,52]. Further, the reduced freedom for users to generate content is contradicting with e.g.…”
Section: Discussion Implications and Recommendationsmentioning
confidence: 99%
“…the feeling of 'anxiety' can further escalate when the question of distribution was prior placed with the employees' supervisor, or the latter needs to intervene if a discussion takes a wrong way due to missing cues [58]. Another UGC distribution barrier can originate from professional users more self-oriented and calculated profile in their contributing and sharing behavior [52]. Moreover, the self-orientation might make it difficult to build the proclaimed common basis which eventually leads to the stewardship phenomenon.…”
Section: Discussion Implications and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation